2019
DOI: 10.1177/2347631119840542
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Emotional Intelligence Competencies in Effective Teaching and Teacher’s Performance in Higher Education

Abstract: The relevance of emotions in teaching is now a widely studied aspect, although contemplation on how the teachers are able to realize, regulate and control their emotions is being deliberated upon. The article attempts to understand the concept of emotional intelligence (EI) in higher education teachers and how it can be incorporated in effective teaching as emotional intelligence competencies (EIC) for superior performance. The technique of structural equation modelling (SEM) has been applied to validate and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 41 publications
(24 reference statements)
1
17
0
2
Order By: Relevance
“…It is supported that EI has a strong correlation with job performance (Anari, 2012;Dulewicz et al, 2005;Mohamad & Jais, 2016;Nguyen et al, 2019;Pekaa et al, 2017;Van Rooy & Viswesvaran, 2004;Wong & Law, 2002) and especially with classroom performance (Kaur et al, 2019;Sue-Chan & Latham, 2004), teacher effectiveness (Kaur et al, 2019;Ramana, 2013;Salami, 2007;Soanes & Sungoh, 2019) and principals' performance (Williams, 2008). Iordanoglou (2007) in her research among 332 primary education teachers in Greece found that EI has a positive effect on teachers' performance and a strong positive effect on job commitment and satisfaction.…”
Section: Emotions and Emotional Intelligence (Ei)mentioning
confidence: 91%
“…It is supported that EI has a strong correlation with job performance (Anari, 2012;Dulewicz et al, 2005;Mohamad & Jais, 2016;Nguyen et al, 2019;Pekaa et al, 2017;Van Rooy & Viswesvaran, 2004;Wong & Law, 2002) and especially with classroom performance (Kaur et al, 2019;Sue-Chan & Latham, 2004), teacher effectiveness (Kaur et al, 2019;Ramana, 2013;Salami, 2007;Soanes & Sungoh, 2019) and principals' performance (Williams, 2008). Iordanoglou (2007) in her research among 332 primary education teachers in Greece found that EI has a positive effect on teachers' performance and a strong positive effect on job commitment and satisfaction.…”
Section: Emotions and Emotional Intelligence (Ei)mentioning
confidence: 91%
“…For the mediating variable, which was job satisfaction, it was measured using a previous study by Amalini et al, (2016), which consisted of 5 items. Then for the first independent variable, which was emotional intelligence, it was measured using a previous study by Kaur et al, (2019), which consisted of 4 items. For the second independent variable, which was intellectual intelligence, it was measured using a previous study by Mantu et al, (2018), which consisted of 5 items.…”
Section: Methodsmentioning
confidence: 99%
“…Teachers must develop the profession as a dignified profession by showing professional teaching performance. Teachers must have the knowledge, skills and attitudes that form the basis for the realization of effective teacher performance (Kaur et al, 2019). Teaching performance contributes very significantly to the effectiveness of learning Guskey (2003); Mihǎescu & Andron (2019) and becomes a major factor in influencing student outcomes (Aaronson et al, 2007;Goldhaber et al, 2010).…”
Section: Introductionmentioning
confidence: 99%